Urban planning at the micro scale considering transport energy dependence - Saunders, Michael James (2010)
High urban transport energy consumption is directly influenced by the level of transport energy dependence of urban forms and transport systems. Despite the introduction of new land use policies and vehicle technologies, dramatic reductions in urban transport energy dependence are not yet being observed. It is proposed that stricter land use regulations coupled with new GIS tools are required that specifically tackle the energy dependence issue. The objective of this project is to design a GIS tool that could be used within an urban development framework to dramatically reduce urban transport energy dependence. A tool was developed and named the Transport Energy Specification (TES). The TES measures urban transport energy dependency from travel behaviour, mode use and spatial data inputs. The TES is designed to be used as an energy based land-use regulation inside an urban development framework by specifying a maximum allowable energy dependency limit for land use modifications in existing urban areas and new developments. Implementation of the energy dependency land use regulation will be achieved through zoning and providing financial or other incentives for the specific desired land use activities (residential, supermarkets, kindergartens etc.). Trials were performed in Germany, New Zealand and Brazil, allowing different urban neighbourhoods and transport systems to be measured with the TES energy dependency measurement tool. The measurements confirmed similar findings from previous researchers regarding the benefits of high density areas and mixed activities in urban areas. Further analysis, trials and workshops with local governments will set in motion the process of including the TES into future urban development policy.